Wave run-up on permeable fixed reveted slopes - I.G. Kantardgi (Инженерно-строительный журнал, 2014)
A numerical model of surface wave movement and water filtration in saturated-unsaturated porous medium has been developed. The model can be used to define the parameters of the wave run-up on the slope protected with a permeable fixed layer. The model is applied to determine positions of the free wave surface at the different times, including such parameters as the height of wave run-up and wave run-down on the slope. In addition, both flow velocity field in the upper protected layer and moisture distribution in the soil body of the slope were defined.